Accomodative Multiculturalism: Alternatif Pendekatan terhadap Masalah Keragaman di Asia Tenggara - Sundrijo, Dwi Ardhanariswari (UI Scholars Hub, 2007)
This paper will explore the Asian way of dealing with religious, ethnic, and cultural diversity and how it dif fers from the Western liberal democratic model of multiculturalism. As argued by Samuel Huntington, glob alization is causing increasing interactions between peoples who previously would not have had any interac tion with each other. These interactions intensify identity consciousness and awareness of differences. In South-East Asia, as in other parts of the world, this means the rise of indigenous ri hts, majority-minority g power-sharing and the need to reconceptualize the idea of diversity and citizenship. The paper will examine how South-East Asian people would approach these issues, using mainly their cultural and reli iou tools. These tools are often referred to and are widely accepted as Asian Values, and include concepts such as har mony, concensus and commonality. The paper will also show that multiculturalism in Asia may not fit the concepts and models of Western's (liberal) multiculturalism.